Knowledge of AIDS and HIV transmission among drug users in Rio de Janeiro, Brazil - Clair Scott; Silva Cosme MFP; Singer Merril; Bertoni Neilane; Malta Monica; Bastos Francisco I (BMC, 2011)
Abstract Background Proper knowledge of HIV transmission is not enough for people to adopt protective behaviors, but deficits in this information may increase HIV/AIDS vulnerability. Objective To assess drug users' knowledge of HIV/AIDS and the possible association between knowledge and HIV testing. Methods A Cross-sectional study conducted in 2006/7 with a convenience sample of 295 illicit drug users in Rio de Janeiro, assessing knowledge on AIDS/HIV transmission and its relationship with HIV testing. Information from 108 randomly selected drug users who received an educational intervention using cards illustrating situations potentially associated with HIV transmission were assessed using Multidimensional Scaling (MDS). Results Almost 40% of drug users reported having never used condoms and more than 60% reported not using condoms under the influence of substances. Most drug users (80.6%) correctly answered that condoms make sex safer, but incorrect beliefs are still common (e.g. nearly 44% believed HIV can be transmitted through saliva and 55% reported that HIV infection can be transmitted by sharing toothbrushes), with significant differences between drug users who had and who had not been tested for HIV. MDS showed queries on vaginal/anal sex and sharing syringes/needles were classified in the same set as effective modes of HIV transmission. The event that was further away from this core of properly perceived risks referred to blood donation, perceived as risky. Other items were found to be dispersed, suggesting inchoate beliefs on transmission modes. Conclusions Drug users have an increased HIV infection vulnerability compared to the general population, this specific population expressed relevant doubts about HIV transmission, as well as high levels of risky behavior. Moreover, the findings suggest that possessing inaccurate HIV/AIDS knowledge may be a barrier to timely HIV testing. Interventions should be tailored to such specific characteristics.